Pattern of ocular tumors in the eastern region of Nepal - Lavaju, P; Arya, SK; Sinha, A; Pandey, S; Adhikari, S; Shrestha, BG; Chetan, S; T, Lidunka Agarwal (Nepalese Journal of Ophthalmology, 2010)
Background: Ocular tumors are commonly encountered in ophthalmic practice. Objective: To study the clinical pattern of ocular tumors in the eastern region of Nepal. Materials and methods: The hospital records of patients with ocular tumors treated at B P Koirala Institute of Health Sciences in the eastern region of Nepal over a period of 5 years (April 2003 - March 2008) were studied retrospectively. Results: Of 115 consecutive patients with ocular tumors, 40 (34.75%) were below the age of 21 years, 41 (35.65%) were in the age group of 21-50 years and 34 (29.56%) of age above 50 years. There were 48 (41.73%) and 67 (58.26%) patients with benign and malignant tumors respectively. The common benign tumors were conjunctival papilloma, dermoid cysts, nevus, cystic lesions and hemangioma. Among the malignant tumors, basal cell carcinoma was the commonest (22.38%). Retinoblastoma was the most common ocular malignant tumor in the pediatric age group (88.8%). Basal cell carcinoma was the commonest eyelid malignancy 53.57%. Conclusion: Conjunctival papilloma, dermoid cysts, nevus, cystic lesions and hemangioma are common benign ocular tumors, whereas basal cell carcinoma and retinoblastoma are the commonest ocular malignancies in adults and children respectively. Key words: ocular malignancy; retinoblastoma; basal cell carcinoma DOI: 10.3126/nepjoph.v1i1.3667 Nep J Oph 2009;1(1):9-12